Accuracy of Commodity Finger Tracking Systems for Virtual Reality Head-Mounted Displays - Schneider, Daniel; Otte, Alexander; Kublin, Axel Simon; Kristensson, Per Ola; Ofek, Eyal; Pahud, Michel; Martschenko , Alexander; Grubert, Jens (IEEE VR 2020, 2020)
Representing users' hands and fingers in virtual reality is crucial for many tasks. Recently, virtual reality head-mounted displays, capable of camera-based inside-out tracking and finger and hand tracking, are becoming popular and complement add-on solutions, such as Leap Motion. However, interacting with physical objects requires an accurate grounded positioning of the virtual reality coordinate system relative to relevant objects, and a good spatial positioning of the user's fingers and hands. To better understand the capabilities of Virtual Reality headset finger tracking, we ran a controlled experiment comparing commodity hand and finger tracking systems (HTC Vive and Leap Motion) and report on the accuracy of commodity hand tracking.